FORCED DEFENSE OF THE CRIME OF THEFT ACCORDING TO THE KUHP FROM THE PERSPECTIVE OF ISLAMIC LAW - As’ad, Muh. Fadel; Gassing HT, Abd. Qadir; Syamsuddin, Rahman (PT. Altin Riset Publishing, 2025)
The purpose of this study is to reveal self-defense according to Islamic law and the Criminal Code article as well as the view of Islamic law on forced defense from the crime of theft based on the Criminal Code. This research is qualitative, the type of research is library research. The data collection method used is a literature study. The results showed that; 1) Islamic law views theft as a serious crime with strict hudud sanctions, while in the Indonesian Criminal Code, theft is regulated by imprisonment or fines according to the severity of the case. 2) Forced defense in the context of theft is recognized by both legal systems, with Islam emphasizing the obligation to defend oneself from arbitrariness, and the Criminal Code allowing self-defense with proportional action. 3) Forced defense regulated in the Criminal Code Article is largely per Islamic law, the person who defends himself gets legal protection, the defense must be proportional and the defense is carried out if there is no other way to avoid danger.